Integrative-Multidimensional Science Paradigm: A Perspective of Islamic Epistemology - Himyari Yusuf; Muhammad Aqil Luthfan; M Baharudin (Journal of Islamic Studies and Humanities, 2019)
Science and human life are inseparable. Without science, human life cannot develop properly. Thus, epistemologically, humans must be placed as the basic foundation of science; that is, humans who have religious and spiritual dimensions equipped with sensory, reason, intuition, and revelation potentials. These dimensions and potentials are the main structure and characteristics of integrative-multidimensional science. This type of science is quite different from modern and contemporary science developed by the West. Western science has reduced the dimensions and potentials of humans into materialistic and mechanical beings; that is, humans who do not have spiritual nor metaphysical dimensions. The Western science is no longer meant for humanity, but for science itself. This study seeks to examine the structure and characteristics of integrative-multidimensional science from the perspective of Islamic epistemology. It makes use of philosophical methods which involve descriptive analysis, interpretation, reflection, and hermeneutic circles. After reviewing the main points of the problem, the study argues that the structure and characteristics of integrative-multidimensional science are ontologically monodualism. In this sense, material dimensions (jasadiyah) and immaterial dimensions (ruhaniyah) are seen as a unit that is synergistic and supporting each other. All the basic human potentials and revelation are the foundation of science. Each of them is seen as an inseparable part. Therefore, in the perspective of Islamic epistemology, integrative-multidimensional science is considered relevant to and connected with the Islamic science.